Intellectual capital and organizational performance: The mediating role of performance measurement system / Kaveh Asiaei - Asiaei, Kaveh (2014)

(untitled)
Globally, information-age economy has superseded the industrial and retail economy. That is, the economy has shifted from an industrial economy, primarily based on physical capital, to an economy based on intellectual capital (henceforth referred to as IC). The effective use of IC factors mainly includes knowledge, relationships, and intellectual property is considered as a cornerstone for the value creation in today's hyper-competitive environment. The central concern which motivates the current study is stemming from the intangible nature of the IC. There is a limited insight on how different types of intangible resources are managed by the firm in a way that such competitive advantage is gained and sustained. However, despite the unobservable nature of IC, the organizations possess other more readily observable feature, which is labeled as organizational control system in general and performance measurement system in particular, that can be used to illuminate the properties and use of its knowledge; Regardless of how control systems are defined, they have a critical feature that has overlooked in the literature: their ability to manage the flow of knowledge and IC inside the organizations. A survey questionnaire was used to collect data for this research. The structural equation modeling (PLS) was employed to examine the associations hypothesized. This study suggests findings according to a sample of Iranian public listed companies which indicated that there is a significant association between the extent of investment in IC and organizational performance overall. Besides, IC level is strongly related to the extent use of certain performance measurement usage either in terms of diversity of measurement or the balanced use of interactive and diagnostic PMS. More importantly, the findings revealed that the emphasis lay upon the use of certain PMS matters given the fact that they mediate the association between the IC and organizational performance. As expected, organizations reflecting more level of IC, and in turn, tend to put value on the use of multiple performance measures as well as the balanced use of interactive and diagnostic PMS would achieve significantly superior performance. Relying on the one of the seminal conceptualizations of IC and from the contingency lens, this study also sets out to determine the effect of two antecedent factors, namely organizational culture and trust on the level of others four IC components. The results provided evidence that culture is associated with human and structural capital. Also, organizations reflecting a greater extent of trust tend to have a higher level of IC overall. This study provides implications to both the theoretical and practical perspectives. From the theoretical angle, this study adopts a more comprehensive IC framework than previous research through supplementing the three general IC components by organizational culture, trust, and social capital. For practical prospects, this study provides some useful guidance to practitioners and organizations in adopting suitable management accounting practices (especially the types of PMS) particularly appropriate for the level of IC in organizations, with the purpose of taking full advantage of their intangible assets.Globally, information-age economy has superseded the industrial and retail economy. That is, the economy has shifted from an industrial economy, primarily based on physical capital, to an economy based on intellectual capital (henceforth referred to as IC). The effective use of IC factors mainly includes knowledge, relationships, and intellectual property is considered as a cornerstone for the value creation in today's hyper-competitive environment. The central concern which motivates the current study is stemming from the intangible nature of the IC. There is a limited insight on how different types of intangible resources are managed by the firm in a way that such competitive advantage is gained and sustained. However, despite the unobservable nature of IC, the organizations possess other more readily observable feature, which is labeled as organizational control system in general and performance measurement system in particular, that can be used to illuminate the properties and use of its knowledge; Regardless of how control systems are defined, they have a critical feature that has overlooked in the literature: their ability to manage the flow of knowledge and IC inside the organizations. A survey questionnaire was used to collect data for this research. The structural equation modeling (PLS) was employed to examine the associations hypothesized. This study suggests findings according to a sample of Iranian public listed companies which indicated that there is a significant association between the extent of investment in IC and organizational performance overall. Besides, IC level is strongly related to the extent use of certain performance measurement usage either in terms of diversity of measurement or the balanced use of interactive and diagnostic PMS. More importantly, the findings revealed that the emphasis lay upon the use of certain PMS matters given the fact that they mediate the association between the IC and organizational performance. As expected, organizations reflecting more level of IC, and in turn, tend to put value on the use of multiple performance measures as well as the balanced use of interactive and diagnostic PMS would achieve significantly superior performance. Relying on the one of the seminal conceptualizations of IC and from the contingency lens, this study also sets out to determine the effect of two antecedent factors, namely organizational culture and trust on the level of others four IC components. The results provided evidence that culture is associated with human and structural capital. Also, organizations reflecting a greater extent of trust tend to have a higher level of IC overall. This study provides implications to both the theoretical and practical perspectives. From the theoretical angle, this study adopts a more comprehensive IC framework than previous research through supplementing the three general IC components by organizational culture, trust, and social capital. For practical prospects, this study provides some useful guidance to practitioners and organizations in adopting suitable management accounting practices (especially the types of PMS) particularly appropriate for the level of IC in organizations, with the purpose of taking full advantage of their intangible assets.Globally, information-age economy has superseded the industrial and retail economy. That is, the economy has shifted from an industrial economy, primarily based on physical capital, to an economy based on intellectual capital (henceforth referred to as IC). The effective use of IC factors mainly includes knowledge, relationships, and intellectual property is considered as a cornerstone for the value creation in today's hyper-competitive environment. The central concern which motivates the current study is stemming from the intangible nature of the IC. There is a limited insight on how different types of intangible resources are managed by the firm in a way that such competitive advantage is gained and sustained. However, despite the unobservable nature of IC, the organizations possess other more readily observable feature, which is labeled as organizational control system in general and performance measurement system in particular, that can be used to illuminate the properties and use of its knowledge; Regardless of how control systems are defined, they have a critical feature that has overlooked in the literature: their ability to manage the flow of knowledge and IC inside the organizations. A survey questionnaire was used to collect data for this research. The structural equation modeling (PLS) was employed to examine the associations hypothesized. This study suggests findings according to a sample of Iranian public listed companies which indicated that there is a significant association between the extent of investment in IC and organizational performance overall. Besides, IC level is strongly related to the extent use of certain performance measurement usage either in terms of diversity of measurement or the balanced use of interactive and diagnostic PMS. More importantly, the findings revealed that the emphasis lay upon the use of certain PMS matters given the fact that they mediate the association between the IC and organizational performance. As expected, organizations reflecting more level of IC, and in turn, tend to put value on the use of multiple performance measures as well as the balanced use of interactive and diagnostic PMS would achieve significantly superior performance. Relying on the one of the seminal conceptualizations of IC and from the contingency lens, this study also sets out to determine the effect of two antecedent factors, namely organizational culture and trust on the level of others four IC components. The results provided evidence that culture is associated with human and structural capital. Also, organizations reflecting a greater extent of trust tend to have a higher level of IC overall. This study provides implications to both the theoretical and practical perspectives. From the theoretical angle, this study adopts a more comprehensive IC framework than previous research through supplementing the three general IC components by organizational culture, trust, and social capital. For practical prospects, this study provides some useful guidance to practitioners and organizations in adopting suitable management accounting practices (especially the types of PMS) particularly appropriate for the level of IC in organizations, with the purpose of taking full advantage of their intangible assets.Globally, information-age economy has superseded the industrial and retail economy. That is, the economy has shifted from an industrial economy, primarily based on physical capital, to an economy based on intellectual capital (henceforth referred to as IC). The effective use of IC factors mainly includes knowledge, relationships, and intellectual property is considered as a cornerstone for the value creation in today's hyper-competitive environment. The central concern which motivates the current study is stemming from the intangible nature of the IC. There is a limited insight on how different types of intangible resources are managed by the firm in a way that such competitive advantage is gained and sustained. However, despite the unobservable nature of IC, the organizations possess other more readily observable feature, which is labeled as organizational control system in general and performance measurement system in particular, that can be used to illuminate the properties and use of its knowledge; Regardless of how control systems are defined, they have a critical feature that has overlooked in the literature: their ability to manage the flow of knowledge and IC inside the organizations. A survey questionnaire was used to collect data for this research. The structural equation modeling (PLS) was employed to examine the associations hypothesized. This study suggests findings according to a sample of Iranian public listed companies which indicated that there is a significant association between the extent of investment in IC and organizational performance overall. Besides, IC level is strongly related to the extent use of certain performance measurement usage either in terms of diversity of measurement or the balanced use of interactive and diagnostic PMS. More importantly, the findings revealed that the emphasis lay upon the use of certain PMS matters given the fact that they mediate the association between the IC and organizational performance. As expected, organizations reflecting more level of IC, and in turn, tend to put value on the use of multiple performance measures as well as the balanced use of interactive and diagnostic PMS would achieve significantly superior performance. Relying on the one of the seminal conceptualizations of IC and from the contingency lens, this study also sets out to determine the effect of two antecedent factors, namely organizational culture and trust on the level of others four IC components. The results provided evidence that culture is associated with human and structural capital. Also, organizations reflecting a greater extent of trust tend to have a higher level of IC overall. This study provides implications to both the theoretical and practical perspectives. From the theoretical angle, this study adopts a more comprehensive IC framework than previous research through supplementing the three general IC components by organizational culture, trust, and social capital. For practical prospects, this study provides some useful guidance to practitioners and organizations in adopting suitable management accounting practices (especially the types of PMS) particularly appropriate for the level of IC in organizations, with the purpose of taking full advantage of their intangible assets.Globally, information-age economy has superseded the industrial and retail economy. That is, the economy has shifted from an industrial economy, primarily based on physical capital, to an economy based on intellectual capital (henceforth referred to as IC). The effective use of IC factors mainly includes knowledge, relationships, and intellectual property is considered as a cornerstone for the value creation in today's hyper-competitive environment. The central concern which motivates the current study is stemming from the intangible nature of the IC. There is a limited insight on how different types of intangible resources are managed by the firm in a way that such competitive advantage is gained and sustained. However, despite the unobservable nature of IC, the organizations possess other more readily observable feature, which is labeled as organizational control system in general and performance measurement system in particular, that can be used to illuminate the properties and use of its knowledge; Regardless of how control systems are defined, they have a critical feature that has overlooked in the literature: their ability to manage the flow of knowledge and IC inside the organizations. A survey questionnaire was used to collect data for this research. The structural equation modeling (PLS) was employed to examine the associations hypothesized. This study suggests findings according to a sample of Iranian public listed companies which indicated that there is a significant association between the extent of investment in IC and organizational performance overall. Besides, IC level is strongly related to the extent use of certain performance measurement usage either in terms of diversity of measurement or the balanced use of interactive and diagnostic PMS. More importantly, the findings revealed that the emphasis lay upon the use of certain PMS matters given the fact that they mediate the association between the IC and organizational performance. As expected, organizations reflecting more level of IC, and in turn, tend to put value on the use of multiple performance measures as well as the balanced use of interactive and diagnostic PMS would achieve significantly superior performance. Relying on the one of the seminal conceptualizations of IC and from the contingency lens, this study also sets out to determine the effect of two antecedent factors, namely organizational culture and trust on the level of others four IC components. The results provided evidence that culture is associated with human and structural capital. Also, organizations reflecting a greater extent of trust tend to have a higher level of IC overall. This study provides implications to both the theoretical and practical perspectives. From the theoretical angle, this study adopts a more comprehensive IC framework than previous research through supplementing the three general IC components by organizational culture, trust, and social capital. For practical prospects, this study provides some useful guidance to practitioners and organizations in adopting suitable management accounting practices (especially the types of PMS) particularly appropriate for the level of IC in organizations, with the purpose of taking full advantage o